Winds of change blowing towards BN - Borneo Post, (KK) (Borneo Post (kk), 2012)
KUALA LUMPUR: Choosing the tagline of 'Fulfilling Promises' as the foremost important agenda, the Barisan Nasional (BN) has touched the hearts of many Malaysians regardless of age, gender, religion and living standards with continuous efforts for the betterment of all.